Comparative metagenomics at Solfatara and Pisciarelli hydrothermal systems in Italy reveal that ecological differences across substrates are not ubiquitous - Ifeoma R. Ugwuanyi; Marilyn L. Fogel; Roxane Bowden; Andrew Steele; Giuseppe De Natale; Giuseppe De Natale; Claudia Troise; Claudia Troise; Renato Somma; Renato Somma; Monica Piochi; Angela Mormone; et al. (Frontiers in Microbiology, 2023)
IntroductionContinental hydrothermal systems (CHSs) are geochemically complex, and they support microbial communities that vary across substrates. However, our understanding of these variations across the complete range of substrates in CHS is limited because many previous studies have focused predominantly on aqueous settings.MethodsHere we used metagenomes in the context of their environmental geochemistry to investigate the ecology of different substrates (i.e., water, mud and fumarolic deposits) from Solfatara and Pisciarelli.Results and DiscussionResults indicate that both locations are lithologically similar with distinct fluid geochemistry. In particular, all substrates from Solfatara have similar chemistry whereas Pisciarelli substrates have varying chemistry; with water and mud from bubbling pools exhibiting high SO42− and NH4+ concentrations. Species alpha diversity was found to be different between locations but not across substrates, and pH was shown to be the most important driver of both diversity and microbial community composition. Based on cluster analysis, microbial community structure differed significantly between Pisciarelli substrates but not between Solfatara substrates. Pisciarelli mud pools, were dominated by (hyper)thermophilic archaea, and on average, bacteria dominated Pisciarelli fumarolic deposits and all investigated Solfatara environments. Carbon fixation and sulfur oxidation were the most important metabolic pathways fueled by volcanic outgassing at both locations. Together, results demonstrate that ecological differences across substrates are not a widespread phenomenon but specific to the system. Therefore, this study demonstrates the importance of analyzing different substrates of a CHS to understand the full range of microbial ecology to avoid biased ecological assessments.